HUBUNGAN SENAM HAMIL DENGAN KEJADIAN PERSALINAN LAMA KALA I PADA IBU BERSALIN DI KLINIK PRATAMA RATNA KOMALA BEKASI - Wati, Puri Kresna (STIKes Medistra Indonesia, 2021)
The prolonged first stage is labor in which the latent phase lasts more than 8 hours and in the active phase the rate of dilatation is inadequate or variable, less than 1 cm every hour for at least 2 hours after the progress of labor. Pregnancy exercise is a fitness program intended for pregnant women. Exercises in pregnancy exercise are specifically designed to make pregnant women healthy and fit, reduce complaints that arise during pregnancy, and prepare physically and psychologically for mothers to face childbirth. This study aims to determine the relationship between pregnancy exercise and the incidence of prolonged labor in the first stage of childbirth at the Ratna Komala Primary Clinic Bekasi in 2019. This study is a quantitative type of research using a cross sectional research design. The results showed that most of the respondents whose labor was not long were 22 (66.7%) respondents compared to 11 (33.3%) respondents whose labor was long. There is a relationship between pregnancy exercise and the incidence of prolonged labor in the 1st stage of maternity at the Pratama Ratna Komala Clinic, Bekasi in 2019. Researchers suggest that pregnancy exercise should be performed on pregnant women with the third trimester of gestation around 28-30 weeks of gestation with a regular frequency of 3 times per week. a week, and perform the movements correctly according to the instructions that have been given.